Noradrenaline and dobutamine effects on the volume expansion with normal saline in rabbits subjected to hemorrhage - Ramalho, Gualter Lisboa [UNESP]; Vane, Matheus Fachini; Lima, Luciana Cavalcanti; Vane, Lucas Fachini [UNESP]; Amorim, Rosa Beatriz [UNESP]; Domingues, Maria Aparecida [UNESP]; de Moraes, José Mariano Soares; de Carvalho, Lídia Raquel [UNESP]; Tanaka, Pedro Paulo; Vane, Luiz Antonio [UNESP] (FapUNIFESP (SciELO), 2016)
PURPOSE: To evaluate the effects of dobutamine (DB), noradrenaline (NA), and their combination (NADB), on volume retention in rabbits submitted to hemorrhage. METHODS: Thirty six rabbits were randomly divided into 6 groups: SHAM, Control, Saline, DB, NA, DB+NA. All the animals, except for SHAM, were subjected to hemorrhage of 25% of the calculated blood volume. Control animals were replaced with their own blood. The other groups received NSS 3 times the volume withdrawn. The intravascular retention, hematocrit, diuresis, central venous pressure, mean arterial pressure, NGAL, dry-to-wet lung weight ratio (DTWR) and the lung and kidney histology were analyzed. RESULTS: Replacement with NSS and NA, DB or NA+DB did not produce differences in the intravascular retention. After hemorrhage, the animals presented a significant decrease in the MAP and CVP, which were maintained until volume replacement. Regarding NGAL, dry-to-wet-lung-weight ratio, lung and kidney histology, there were no statistical differences between the groups. CONCLUSION: The use of noradrenaline, dobutamine or their combination did not increase the intravascular retention of volume after normal saline infusion.
Keywords: Catecholamines; Hemorrhage; Plasma volume; Rabbits